Exploring the final examination test item characteristics of Pancasila and civic education - Syarief Fajaruddin; Heri Retnawati; Eri Yusron; Vinni Sofyaningsih (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
The study aims at exploring the final examination test items to identify the quality of the test items as an evaluation instrument. The study is descriptive quantitative research that pursues the document analysis to view the Final Semester Examination test item characteristics of Pancasila and Civic Education in Grade VIII of State Madrasah Tsanawiyah (Madrasah Tsanawiyah Negeri 3 or MTs Negeri 3) in the Regency of Gunungkidul, the Province of Yogyakarta Special Region, within the 2020/2021 Academic Year. In analyzing the data that have been collected, the researchers have adopted the approach of Item Response Theory (*IRT) using the R Program assistance. The results of the study show that the Final Semester Examination test items of Pancasila and Civic Education are more appropriate to be analyzed by using the SPL Model. The degree of difficulty for these items falls into the “Good” quality within the range -4.0 until +4.0. On the contrary, the item discrimination capacity ranges between 0.079 and 4.891 with the “Moderate” quality.